(untitled) (Observatorio Económico, 2012)
For the first time, a possible slowdown of the Chinese economy is in view. China used to be the engine that kept running when Europe, Japan, or the United States faltered. What could happen to us in this scenario? Chile, 2012. Will the growth of 2011 be repeated, or will the economy stagnate as has been happening in other countries? Considering the latest data on inflation, growth (measured by the Imacec, the monthly index of economic activity) and unemployment, the Chilean economy would appear to be approaching full employment. Continue reading...